Microwave-assisted facile fabrication of porous poly (glycerol sebacate) scaffolds. Issue 7 (13th June 2018) - Lee, Soo Hyon; Lee, Kee-Won; Gade, Piyusha S.; Robertson, Anne M.; Wang, Yadong
Abstract: The biodegradable elastomeric polyester poly(glycerol sebacate) (PGS) was developed for soft-tissue engineering. It has been used in various research applications such as wound healing, cartilage tissue engineering, and vascular grafting due to its biocompatibility and elastomeric properties. However conventional PGS manufacture is generally limited by the laborious reaction conditions needed for curing which requires elevated reaction temperatures, high vacuum and multi-day reaction times. In this study, we developed a microwave irradiation methodology to fabricate PGS scaffolds under milder conditions with curing times that are 8 times faster than conventional methods. In particular, we determined microwave reaction temperatures and times for maximum crosslinking of PGS elastomers, demonstrating that PGS is fully crosslinked using gradual heating up to 160 °C for 3 h. Porosity and mechanical properties of these microwave-cured PGS elastomers were shown to be similar to PGS elastomers fabricated by the conventional polycondensation method (150 °C under 30 Torr for 24 h). To move one step closer to clinical application, we also examined the biocompatibility of microwave-cured PGS using in vitro cell viability assays with primary baboon arterial smooth muscle cells (SMCs). These combined results show microwave curing of PGS is a viable alternative to conventional curing.